Amino Acid Selection Altered Silver Nanoparticles Morphology and Formation of Silver Oxide Layers - Bolat, Şuheda; Sancak, Zafer; Gümüş, Abdurrahman; Yazgan, Idris (MDPI AG, 2025)
Amino acids are not just monomers of proteins, but they can also carry biological functions. L-cysteine (Cys), L-proline (Pro), L-asparagine (Asn), and L-glutamic acid (Glu) were used to evaluate how different amino acid chemistries alter the morphology and size of the silver nanoparticles (AgNPs) synthesized in the presence of two carbohydrate ligands, which were lactose methoxyaniline (LMA) and galactose 5-aminosalicylic acid (G5AS). UV–vis, infrared (IR), High-Resolution Transmission Electron Microscopy (HR-TEM) and X-ray diffraction (XRD) characterizations revealed that the effect of amino acids on the characteristics of the AgNPs showed dependence on the carbohydrate ligand chemistry. In the case of LMA, AgNPs shifted from aggregates to anisotropic nanoparticles, larger aggregates, and a mixture of anisotropic and 1D nanoparticles in the presence of Cys, Glu, Asn and Pro amino acids, respectively. In contrast to this, the introduction of Cys and Asn caused the formation of cluster-like AgNPs and larger rounded nanoparticles, while G5AS-synthesized AgNPs were multigonal 0D particles. Moreover, Glu and Pro contributed the resistance of silver oxide formation on the particles. Antibacterial characterization showed that LMA_Glu_AgNPs were the most effective ones, while LMA_Cys_AgNPs and G5AS_Cys_AgNPs, which were the smallest AgNPs, did not show any significant antibacterial activity.